10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Epilepsy comprises a highly heterogeneous group of neurological disorders unified by a persistent predisposition to recurrent seizures, yet driven by remarkably diverse genetic, molecular, and network-level mechanisms. Advances in genomic technologies have revealed that epilepsy arises from a multilayered genetic architecture encompassing rare high-penetrance monogenic variants, common polygenic risk factors, brain-restricted somatic mosaicism, and extensive gene-environment interactions. These genetic substrates converge on core biological pathways regulating neuronal excitability, synaptic transmission, metabolic homeostasis, neuroinflammation, and circuit development. In this review, we synthesize contemporary insights into the genetic and molecular pathophysiology of seizures and epilepsy, with emphasis on mechanisms that destabilize excitation-inhibition balance, promote epileptogenesis, and drive pharmacoresistance. We highlight how ion channel dysfunction, synaptic vesicle cycling defects, mTOR pathway hyperactivation, glial and metabolic failure, and inflammatory cascades interact to lower seizure threshold and remodel neural networks. Beyond classical monogenic and polygenic models, we discuss the emerging role of somatic mutations, polygenic modifiers of rare variants, and dynamic brain-state-dependent seizure susceptibility. We further integrate genetic mechanisms with clinical heterogeneity, including age of onset, seizure type, penetrance, pleiotropy, and treatment response, and review translational implications for precision medicine, pharmacogenomics, and emerging molecular therapies such as antisense oligonucleotides, gene regulation strategies, and cell-based interventions. Understanding the genetic architecture of epilepsy is increasingly informing diagnostic pathways, prognostic stratification, and the development of precision-based therapeutic approaches. PLAIN LANGUAGE SUMMARY: Epilepsy genetics extends beyond single-gene disorders and involves multiple interacting layers of genomic variation. In this review, we integrate evidence across rare variants, polygenic risk, somatic mosaicism, and genetic modifiers to provide a broader framework for understanding seizure susceptibility and clinical diversity. By highlighting convergent biological pathways and their effects on neuronal networks, this work supports more refined approaches to epilepsy classification and future precision medicine strategies.